Beryllium contamination and its risk management in terrestrial and aquatic environmental settings. (1st March 2023) - Bolan, Shiv; Wijesekara, Hasintha; Tanveer, Mohsin; Boschi, Vanessa; Padhye, Lokesh P.; Wijesooriya, Madhuni; Wang, Lei; Jasemizad, Tahereh; Wang, Chensi; Zhang, Tao; Rinklebe, Jörg; Wang, Hailong; et al.
Abstract: Beryllium (Be) is a relatively rare element and occurs naturally in the Earth's crust, in coal, and in various minerals. Beryllium is used as an alloy with other metals in aerospace, electronics and mechanical industries. The major emission sources to the atmosphere are the combustion of coal and fossil fuels and the incineration of municipal solid waste. In soils and natural waters, the majority of Be is sorbed to soil particles and sediments. The majority of contamination occurs through atmospheric deposition of Be on aboveground plant parts. Beryllium and its compounds are toxic to humans and are grouped as carcinogens. The general public is exposed to Be through inhalation of air and the consumption of Be-contaminated food and drinking water. Immobilization of Be in soil and groundwater using organic and inorganic amendments reduces the bioavailability and mobility of Be, thereby limiting the transfer into the food chain. Mobilization of Be in soil using chelating agents facilitates their removal through soil washing and plant uptake. This review provides an overview of the current understanding of the sources, geochemistry, health hazards, remediation practices, and current regulatory mandates of Be contamination in complex environmental settings, including soil and aquatic ecosystems. Graphical abstract: Image 1 Highlights: Mining and anthropogenic activities are major sources of Be in the environment. High Be concentrations are toxic to ecosystems and human health. Be contamination occurs via atmospheric deposition on aboveground plant parts. Immobilization using soil amendments is a practical approach for Be-remediation. Be-remediation via phyto- and microbial means can be environmentally sustainable.